BaptisteVandecrux/SEB_Firn_model: GEUS surface energy balance and firn model v0.3 - Vandecrux, Baptiste (Zenodo, 2021)
GEUS model as used in : Baptiste Vandecrux, William Colgan, Anne M. Solgaard, Jørgen Peder Steffensen and Nanna B. Karlsson: Firn evolution at Camp Century, Greenland: 1966-2100, Frontiers in Earth Science, https://doi.org/10.3389/feart.2021.578978, 2020